(untitled) (Bangladesh Journal of Agricultural Research, 2011)
Forty four hyacinth bean genotypes were studied to estimate the variability, heritability, genetic advance and correlation coefficients. There was a large variation among the genotypes for all the characters among which the number of pods per plant had highest (122 to 425). Green pod yield per plant varied from 0.46 kg to 3.45 kg indicating the presence of high yielding genotypes. High genotypic coefficient of variation was obtained for 100-green seed weight, pod yield per plant, number of pods per plant and harvesting duration. The highest heritability was observed for days to first flower (98.39%) followed by days to first harvest (96.1 %).The pod yield per plant also exhibited high heritability of 77.9% with highest genetic advance (68.28) indicating the possibility of selection to improve this traits. Yield of green pods showed highly significant and positive association with number of pods per plant (r=0.71**), individual pod weight (r=0.54**) and harvesting duration (r=0.198*), which indicates the importance of these characters during selection for high yielding genotypes in hyacinth bean. Keywords: Genetic variability; heritability; hyacinth bean. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9262 BJAR 2011; 36(2): 351-356